Stringer Legality and Jurnalistic Works in Television Media (Legalitas Stringer dan Karya Jurnalistik dalam Media Televisi) - didik haryadi santoso; rani dwi lestari (BBPSDMP KOMINFO MAKASSAR, 2017)
Recently, Media of Television industry is growing rapidly. There are many problems arise, including the rise of contracted media workers who are separated from work agreement system with media companies. It has a duty to get and excavate news of television media without being clearly bound with media companies. This practice is known as stringer. This research attempts to examine the practice of stringer, stringer legality, and the legality of the work of journalistic video produced. Both of them become long term materials in discussing media employment legislation. This study uses the case study method of Robert K. Yin with single case study design that consists of several sub-unit analyses. The purposes of this research are: to understand more deeply about the practice of stringer, the legality of the stringer and the legality of resulting video journalistic work produced. The results of this case show that firstly, the practice of stringer in the television media becomes as a practice of mutualism symbiotic between stringer, contributors in the region and media companies. Secondly, the stringer position in media companies is not recognized as an official work even though their efforts and their works are spread in national media. The practice of stringer is not legal because it is in the vagueness of value, rights and obligations as an official media worker. Thirdly, the legality of the work, the journalistic videos are produced by stringer, it is illegal although claimed to be the work of official journalistic. It contravenes of code of journalistic ethics, because the preaching of the work that has been published in a media is basically protected as a result of copyright and included in the intellectual property rights category. Industri media televisi berkembang pesat, kebutuhan tenaga kerja media turut meningkat, sehingga memungkinkan lahir dan hadirnya pekerja-pekerja media kontrak yang lepas dari sistem perjanjian kerja dengan perusahaan media. Mereka bertugas mencari dan menggali berita tanpa terikat secara jelas dengan perusahaan media. Praktik ini dikenal dengan istilah stringer. Persoalan yang muncul dan menjadi fokus penelitian ini, yaitu legalitas stringer dan legalitas karya video jurnalistik. Keduanya menjadi bahan dalam membahas tentang undang-undang tenaga kerja media. Penelitian ini menggunakan metode studi kasus Robert K.Yin dengan desain studi kasus tunggal terjalin yang terdiri dari beberapa sub unit analisis. Hasil penelitian ini menunjukkan bahwa Pertama, praktek stringer dalam industri media televisi menjadi semacam praktik simbiosis mutualisme antara stringer, kontributor di daerah dan perusahaan media. Kedua, posisi stringer dalam perusahaan media tidak diakui sebagai pekerja resmi meskipun tenaga dan karyanya tersebar di media nasional. Praktik stringer ini tidak legal sebab berada pada ketidakjelasan nilai, hak serta kewajibannya sebagai pekerja media yang resmi. Ketiga, secara legalitas karya. Video jurnalistik yang dihasilkan oleh stringer termasuk illegal meskipun diklaim sebagai karya jurnalis resmi. Hal ini melanggar kode etik jurnalistik sebab pemberitaan hasil karya yang telah dimuat di media pada dasarnya dilindungi sebagai hasil karya cipta dan masuk dalam kategori intellectual property right.